Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2019)
A large variety of publications involving O- and S-6-membered ring systems have appeared in 2017. The importance of these heterocyclic compounds is highlighted by the huge number of publications on the total synthesis of natural oxygen derivatives and of other communications dedicated to synthetic derivatives. Reviews on stereoselective organocatalytic synthesis of tetrahydropyrans (17EJO4666), of tetrahydropyrans and their application in total synthesis of natural products (17CSR1661), on the synthesis of the less thermodynamically stable 2,6-trans-tetrahydropyrans (17S4899), on enantioselective synthesis of polyfunctionalized pyran and chromene derivatives (17TA1462), and on enantioselective and racemic total synthesis of camptothecins, including the formation of their pyran-2-one ring (17SL1134), have appeared. Advances in the transition metal-catalyzed synthesis of pyran-2/4-ones (17TL263), N-heterocyclic carbene (NHC)-catalyzed achiral synthesis of pyran-2-one, coumarin and (thio)chromone derivatives (17OBC4731), on the synthesis and transformation of 2H-pyran-2-ones (17T2529) and 2-styrylchromones (17EJO3115) into other heterocyclic compounds, have been surveyed. The strategies to build up the tetrahydropyranyl core of brevisamide (17H(95)81) and the reactions of ketyl radicals, generated from carbonyl derivatives under transition-metal photoredox-catalyzed conditions, leading to isochromen- and chroman-type compounds (17CC13093) were disclosed. Developments in the synthesis of pentafluorosulfanyl(chromene and coumarin) derivatives (17TL4803), photoswitchable D9-tetrahydrocannabinol derivatives (17JA18206), and aminobenzopyranoxanthenes with nitrogen-containing rings (17JOC13626) have been studied.